2017
DOI: 10.1080/10408398.2017.1386158
|View full text |Cite
|
Sign up to set email alerts
|

Milk fat globule membrane glycoproteins: Valuable ingredients for lactic acid bacteria encapsulation?

Abstract: The membrane (Milk Fat Globule Membrane - MFGM) surrounding the milk fat globule is becoming increasingly studied for its use in food applications due to proven nutritional and technological properties. This review focuses first on current researches which have been led on the MFGM structure and composition and also on laboratory and industrial purification and isolation methods developed in the last few years. The nutritional, health benefits and techno-functional properties of the MFGM are then discussed. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 119 publications
0
41
0
Order By: Relevance
“…It has been hypothesized that probiotic bacteria (such as members of the Lactobacillus and Bifidobacterium genera) are able to pass from the mammary gland through to the infant colon by adhering to components of the MFGM, suggesting that the MFGM may be a probiotic carrier ( 227 ). Recently, Pannaraj et al ( 228 ) established that bacteria found naturally in breast milk are able to seed the infant gut during the early stages of gut development ( 228 ).…”
Section: Impact On the Infant Gut Microbiotamentioning
confidence: 99%
See 2 more Smart Citations
“…It has been hypothesized that probiotic bacteria (such as members of the Lactobacillus and Bifidobacterium genera) are able to pass from the mammary gland through to the infant colon by adhering to components of the MFGM, suggesting that the MFGM may be a probiotic carrier ( 227 ). Recently, Pannaraj et al ( 228 ) established that bacteria found naturally in breast milk are able to seed the infant gut during the early stages of gut development ( 228 ).…”
Section: Impact On the Infant Gut Microbiotamentioning
confidence: 99%
“…longum , were identified in breast milk and infant feces of the same mother-infant pair, but not in the oral cavity, suggesting that breast milk provides an important inoculum of specific bacteria for seeding the infant gut ( 229 ). Bacteria (including Lactobacillus ) present in milk have been shown to preferentially associate with the MFGM utilizing glycan adhesion factors that enable them to bind to mucin ( 227 ). In addition, bacteria with greater surface hydrophobicity, such as L .…”
Section: Impact On the Infant Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…The composition, health attributes, and biological activity of commercial ingredients containing MFGM, milk phospholipids, or MFGM isolated in the laboratory have been extensively reviewed [2,5,22,25,[53][54][55][56][57][58][59]. Given the complexity of the composition of MFGM, here we present in a differentiated way the available information on health benefits of (a) proteins and (b) lipids, in particular phospholipids.…”
Section: Biological Effects Of Mfgmmentioning
confidence: 99%
“…The evidence around strong interactions between glycoproteins such as MUC1 and a mucin-binding factor on the surface of the bacteria suggests this material for the enhanced encapsulation of probiotics. In addition, the health benefits brought by membrane-specific proteins may also be an advantage (Guerin et al, 2019 ).…”
Section: Nature-assembled Structures In Milkmentioning
confidence: 99%